ANALISIS KINERJA KEUANGAN PT GARDA TUJUH BUANA TBK DITINJAU DARI RASIO LIKUIDITAS DAN RASIO PROFITABILITAS - Sari, Intan Permata (EKONOMIA, 2020)
Faculty of Economics, University of August 17, 1945 Samarinda, Analysis of Financial Performance of PT Garda Tujuh Buana Tbk Judging from the Liquidity Ratio and Profitability Ratio for the period 2013-2017. Under the guidance of Titin Ruliana and Camelia Verahastuti.This study aims to determine: 1) financial performance of PT. Garda TujühBuanaTbk in the period 2013-2017 in terms of Liquidity Ratios (current ratio and quick ratio, 2) financial performance of PT. Garda Tujuh Buana Tbk in the period 2013-2017 in terms of the Profitability Ratio (net profit margin, retention on assets and return on equity). This research shows: 1) Current Ratio has decreased in 2014, 2015, 2016 and 2017 and experienced increase in 2013. 2) Quick Ratio decreased in 2013, 2015 and 2017 and experienced an increase in 2014 and 2016.2) Net Profit Margin decreased in 2013, 2014 and 2017 and increased in 2015 and 2016. 3 ) Return On Assets has decreased in 2013, 2014, 2016 and 2017 and has increased in 2015. 4) Return On Equity has decreased in 2013, 2014, 2016 and 2017 and has increased in 2015. This decline occurs because of the lack of companies in optimizing assets on financial performance, and the profits that are generated are less.